Co-existence of WiFi IEEE802.11a networks - Soon, Han Kuan. (2011)
This report shows the development and analyzing of low-complexity cooperative diversity two-phase protocols that combat fading induced by multipath propagation in wireless networks. The underlying techniques exploit space diversity available through cooperating terminals’ replaying signals for one another. Several strategies employed by the cooperative radios such as fixed relay schemes, amplify-and-forward and decode-and-forward, were discussed for the secondary system to achieve spectrum access along with the primary system.